WAYS TO MINIMIZE VOLUME (WEIGHT) AND INCREASE THE BEARING CAPACITY OF RIGID PAVEMENT - Kolesnikov, Alexander; Tolmacheva, Tatiana (Salehan Institute of Higher Education, 2019)
The objective of research is finding of a possibility economy of rigid pavement weight and volume of material. The subject of the research is a mathematical model of rigid pavement in the form of a multilayer structure on an elastic foundation. The method of a research consists in modeling the behavior of rigid pavement in the form of a set of equations. These equations reflect the change in the stress-strain state of such structures. The system of equations takes into account the geometric nonlinearity of the work of materials and makes it possible to investigate the influence of various parameters on the values of stresses and displacements. Critical force coefficient and stress of shells are calculated by Bubnov-Galerkin. The formation way of the elastic foundation allows modeling the spreading layers with various characteristics. Use of two-layer model allows considering of a surface course and base course of road pavement designing (for example concrete and crushed stone). The graphs show the patterns of change of the stress of rigid pavement when changing the characteristics. The form of rigid pavement allowing to maintain big loadings is exposed to improvement. Findings shows the possibility of optimizing the geometric parameters of the design and achieving the savings in weight and volume of the consumable material.